Investigation of Class of Low Speed Asynchronous Electric Drives - Poska, A.; Rinkeviciene, R.; Meilunas, M. (Elektronika ir Elektrotechnika, 1999)
The new method of investigation of low speed asynchronous electric drives is proposed when the set of parameters corresponding to drive characteristics reflecting this group is formed. The direct problem -determination of displacement of the center of gravity of parameters set due to characteristic feature of linear motor - edge effect is formulated. Solution of direct problem is illustrated by displacement of vector of critical points of mechanic characteristics. The reverse problem is discussed. It's solution allows to determine set of parameters of linear electric motors ensuring required properties of drives.